Incidence and predictors of left ventricular function change following ST-segment elevation myocardial infarction - Liu, Chuanfen; Guo, Meng; Cui, Yuxia; Wu, Manyan; Chen, Hong (Frontiers in Cardiovascular Medicine, 2023)
Aim The purpose of the study was to assess the incidence and predictors of left ventricular function change in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary PCI. Methods 312 patients with STEMI who received primary percutaneous coronary intervention (PCI) between January 2015 and December 2016 were consecutively enrolled in this study. Multiple logistic regression analysis was used to evaluate independent predictors of left ventricular ejection fraction (LVEF) improvement after long-term follow-up. Results We finally analyzed the LVEF change in 186 patients from baseline to follow-up. The mean age was 61.3 ± 12.5 years, with 78.5% being male. The median duration of follow-up after STEMI was 1,021 (389–1,947) days. 54.3% had a decrease in LVEF and 45.7% experienced an improvement in LV function after primary PCI through long-term follow-up. Logistic regression analysis showed lower peak troponin I, non-anterior STEMI, lower baseline LVEF, and no previous myocardial infarction history were independently associated with LVEF improvement. Conclusion 54.3% of patients with STEMI undergoing primary PCI had a decrease in LVEF during long-term follow-up. LVEF recovery can be predicted by baseline characteristics.